(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study analyses the role of the maqasid sharia in guiding the digitalisation of the Islamic economy to strengthen justice, sustainability, and the economic resilience of the ummah, while linking it to the Astagatra framework as the foundation of national resilience. Study Design/Methodology/Approach: This study uses a descriptive qualitative method with content analysis of the latest academic literature on digitalisation, Islamic economics, maqasid sharia, and national resilience. The study is guided by the TSR as a normative foundation and the Dynamic Capability Theory as an adaptive foundation. Findings: Digitalisation strengthens Islamic financial inclusion, social legitimacy, and sustainable development when grounded in the maqasid sharia. TSR emphasises the integration of spiritual values into technological innovation, while dynamic capabilities explain the adaptive capacity of Islamic financial institutions to face disruption in the VUCA era. The integration of Astagatra demonstrates the strengthening of the ideological, economic, socio-cultural, and defence and security dimensions. Originality/Value: This study presents an integrative framework between the maqasid sharia, TSR, dynamic capabilities, and Astagatra, which is still rarely explored. Practical contributions lie in emphasising the measurement of sustainable use and accountable governance so that digitalisation supports community economic resilience and equitable national development.